Examining the Synthesis of Islamic Commercial Principles and Local Customary Practices: A Case Study of Nyambut Sawah Traditions in Tejamari, Banten - Jamaluddin, Jamaluddin; Hayat, Milatul; Masduki, Masduki; Mukarromah, Oom; Jamaludin, Jamaludin (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
The influence stemming from the intersection of local traditions and religious percept manifests itself in the practice of nyambut sawah (paddy cultivation) among the Tejamari community. This practise resembles the utilisation of agricultural land (muzāra’ah) in Islamic commercial law (fiqh mu’āmalah), wherein landowners provide agricultural land to cultivators for cultivation with a profit-sharing system. This article aims to analyse the extent to which the practice of nyambut sawah adopts the principles of Islamic commercial law. This study employs a normative-empirical approach, conducting observations and interviews with eighteen informants. The research finds that the nyambut sawah tradition practiced by the Tejamari community reflects the muzāra’ah contract in fiqh mu’āmalah. The muzāra’ah contract is reflected in five models of profit-sharing systems, wherein the division of tasks, responsibilities, profits, and risks has been mutually agreed upon. Despite differences in opinion regarding the responsibility for the cost of rice milling (ngeprik padi), this practice still maintains values of mutual assistance between landowners and cultivators in overcoming economic difficulties. This article argues that local traditions and religious values can together provide solutions for the sustainability of agricultural activities. [Pengaruh interaksi tradisi lokal dengan agama tampak dalam praktik nyambut sawah di kalangan masyarakat Tejamari. Praktik ini menyerupai pemanfaatan lahan pertanian (muzāra’ah) dalam fikih muamalah, di mana pemilik tanah menyediakan lahan pertanian kepada penggarap untuk ditanami dengan sistem bagi hasil. Artikel ini bertujuan untuk menganalisis sejauh mana praktik nyambut sawah mengadopsi prinsip-prinsip hukum bisnis Islam. Studi ini menggunakan pendekatan normatif-empiris, melakukan observasi dan wawancara dengan delapan belas informan. Penelitian menunjukkan bahwa tradisi nyambut sawah yang dipraktikkan oleh masyarakat Tejamari mencerminkan kontrak muzāra’ah dalam fikih muamalah. Kontrak muzāra’ah tercermin dalam lima model sistem bagi hasil, di mana pembagian tugas, tanggung jawab, keuntungan, dan risiko telah disepakati secara bersama. Meskipun terdapat perbedaan pendapat mengenai tanggung jawab atas biaya ngeprik padi (penggilingan padi), praktik ini tetap mempertahankan nilai-nilai saling tolong-menolong antara pemilik lahan dan penggarap dalam mengatasi kesulitan ekonomi. Artikel ini berargumen bahwa tradisi lokal dan nilai-nilai agama dapat bersama-sama memberikan solusi untuk keberlanjutan kegiatan pertanian.]